Presence of pharmaceutical compounds in groundwater with respect to land use in the vicinity of sampling sites - Kuczyńska, Anna (Geologos, 2019)
The present paper discusses the results of an analysis of the impact of land use on the distribution of pharmaceuticals in groundwater samples collected during a pilot study of the contents of pharmaceuticals and hormones in ground-water taken from the national groundwater monitoring network of the Polish Geological Institute - National Research Institute. Samples were collected during monitoring campaigns from 160 groundwater monitoring sites in various land use types in 2016 and 2017. Samples were analysed for a total of 34 active substances, including natural and synthetic oestrogen hormones, cardiovascular and respiratory medications, analgesics and anti-inflammatories, antidepressants, antimicrobial drugs and anti-epileptics. Our study confirmed the presence of pharmaceuticals in 53 per cent of ground-water samples taken. Data show variations in the distribution of pharmaceuticals depending on land use type, which can thus be employed in pressure analysis and identification of sources of pollution.